2021
DOI: 10.1002/cbdv.202001043
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of n‐Butanol Extract from Viola yedoensis on Immunological Liver Injury

Abstract: Viola yedoensis Makino was used to treat inflammation, viral hepatitis, acute pyogenic infection, and ulcerative carbuncles. However, the protective effect on immunological liver injury (ILI) of V. yedoensis had been rarely reported. This study aimed to explore the protective effect of n‐butanol extract (BE) from V. yedoensis on ILI in vitro and in vivo. In vitro, the BE significantly inhibited the secretions of Hepatitis B surface antigen (HBsAg) and Hepatitis B e antigen (HBeAg) in the HepG2.2.15 cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…(Akter et al, 2020; Liu et al, 2015; Ma & Zhao, 2008). In addition, esculin has been detected in a variety of Asteraceae plants, such as Artemisia capillaris Thunb., Artemisia japonica Thunb., and Artemisia capillaris Thunb., and even fruits Prunus domestica L. and Prunus salicina L. (Chu et al, 2021; Jaiswal et al, 2013). However, the esculin contents of these plants are low.…”
Section: Main Plant Sources Of Esculinmentioning
confidence: 99%
See 3 more Smart Citations
“…(Akter et al, 2020; Liu et al, 2015; Ma & Zhao, 2008). In addition, esculin has been detected in a variety of Asteraceae plants, such as Artemisia capillaris Thunb., Artemisia japonica Thunb., and Artemisia capillaris Thunb., and even fruits Prunus domestica L. and Prunus salicina L. (Chu et al, 2021; Jaiswal et al, 2013). However, the esculin contents of these plants are low.…”
Section: Main Plant Sources Of Esculinmentioning
confidence: 99%
“…Studies have shown that esculin can improve oxidative stress injury by enhancing the activities of SOD and GSH‐PX. Chu et al found that the extract of Viola yedoensis Makino (3–12 g/kg) rich in esculin increased the activities of SOD and GSH‐PX and inhibited the production of malondialdehyde in concanavalin A‐induced mice (Chu et al, 2021). Esculin (12.5–50 mg/kg) protected mice from ethanol‐induced gastric mucosal damage by increasing the level of SOD and decreasing both the myeloperoxidase activity and the malondialdehyde amount (Rios et al, 2010).…”
Section: The Pharmacological Effects Of Esculinmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral hepatitis and autoimmunity hepatitis (AHI) are the most common forms of immune-mediated hepatitis. 1 Chemokine-directed immune cell infiltration plays an essential role in the pathogenesis of immune-mediated hepatic injury. 2 The chemokine C-X3C motif ligand 1 (CX3CL1) and its sole receptor, C-X3C motif receptor 1 (CX3CR1), are involved in the recruitment of monocytes/macrophages and T cells and play critical roles in many diseases.…”
Section: Introductionmentioning
confidence: 99%